Shape memory TiNi powders produced by plasma rotating electrode process for additive manufacturing - CHEN, Gang; ZHAO, Shao-yang; TAN, Ping; YIN, Jing-ou; ZHOU, Quan; GE, Yuan; LI, Zeng-feng; WANG, Jian; TANG, Hui-ping; CAO, Peng (Transactions of Nonferrous Metals Society of China, 2017)
This study aimed to produce spherical TiNi powders suitable for additive manufacturing by plasma rotating electrode process (PREP). Scanning electron microscopy, X-ray diffractometry and differential scanning calorimetry were used to investigate the surface and inner micro-morphology, phase constituent and martensitic transformation temperature of the surface and inner of the atomized TiNi powders with different particle sizes. The results show that the powder surface becomes smoother and the grain becomes finer gradually with decreasing particle size. All the powders exhibit a main B2-TiNi phase, while large powders with the particle size ≥178 μm contain additional minor Ti2Ni and Ni3Ti secondary phases. These secondary phases are a result of the eutectoid decomposition during cooling. Particles with different particle sizes have experienced different cooling rates during atomization. Various cooling rates cause different martensitic transformation temperatures and routes of the TiNi powders; in particular, the transformation temperature decreases with decreasing particle size.